Effective taxation of top incomes in Germany - Stefan Bach; Giacomo Corneo; Viktor Steiner (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
We exploit an exhaustive administrative dataset that includes the individual tax returns of all households in the top percentile of the income distribution in Germany to pin down the effective income taxation of households with very high incomes. Taking tax base erosion into account, we find that the top percentile of the income distribution pays an effective average tax rate of 30.5 percent and contributes more than a quarter of total income tax revenue. Within the top percentile, the effective average tax rate is first increasing and then decreasing with income. Since the 1990s, effective average tax rates for the German super rich have fallen by about a third, with major reductions occurring in the wake of the personal income tax reform of 2001-2005. As a result, the concentration of net incomes at the very top of the distribution has strongly increased in Germany.
Keywords: H24; H26; D31; 330; personal income tax; taxing the rich; effective progressivity